2017
DOI: 10.1016/j.ecolind.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lichen species resistance to atmospheric metal pollution by coupling diversity and bioaccumulation approaches: A new bioindication scale for French forested areas

Abstract: To cite this version:Y. Agnan, A. Probst, N. Séjalon-Delmas. Evaluation of lichen species resistance to atmospheric metal pollution by coupling diversity and bioaccumulation approaches: A new bioindication scale for French forested areas. Ecological Indicators, Elsevier, 2017Elsevier, , 72, pp.99-110. <10.1016Elsevier, /j.ecolind.2016 b s t r a c tIn order to evaluate the metal resistance or sensitivity of lichen species and improve the bioindication scales, we studied lichens collected in eight plottings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 51 publications
(59 reference statements)
3
20
0
2
Order By: Relevance
“…Rich epiphyte vegetation with high species diversity was observed in rural stations, far from sources of pollution. The same observations have been reported by several authors (Batic and Mayrhofer 1996;Cazaux and Saint-Cricq 2010;Das et al 2013;Agnan et al 2017;Khastini et al 2019). This diversity is influenced by important air humidity (Jayalal et al 2015).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Rich epiphyte vegetation with high species diversity was observed in rural stations, far from sources of pollution. The same observations have been reported by several authors (Batic and Mayrhofer 1996;Cazaux and Saint-Cricq 2010;Das et al 2013;Agnan et al 2017;Khastini et al 2019). This diversity is influenced by important air humidity (Jayalal et al 2015).…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, in forest regions in France far from industrial sources, Agnan et al Statistical tests indicated a significant correlation between the values of the LDV indices and those of the IAP; they increase with increasing species diversity and abundance of lichens. This strong correlation could be due to the unique use of frequencies in the LDV calculation method and the ecological index of each species (Q) included in the IAP formula (Loppi et al 2004;Agnan et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations